Chronic Stress‐Induced and Tumor Derived SP1+ Exosomes Polarizing IL‐1β+ Neutrophils to Increase Lung Metastasis of Breast Cancer - Leyi Zhang; Jun Pan; Meijun Wang; Jini Yang; Sangsang Zhu; Lili Li; Xiaoxiao Hu; Zhen Wang; Liwei Pang; Peng Li; Fang Jia; Guohong Ren; et al. (Advanced Science)
Abstract Chronic stress can significantly promote breast cancer progression. When exposed to chronic stress, exosomes released from neural and neuroendocrine cells in the central nervous system are enhanced and modified. However, whether tumor‐derived exosomes (TDEs) are influenced by chronic stress and participate in chronic stress‐mediated distant metastasis remains unclear. Here, it is shown that chronic stress remarkably facilitates the secretion of TDEs and modifies the contents of exosomes by activating the adrenergic β receptor in 4T1 tumor‐bearing mice. Exosomes injection and blockade experiments indicate that exosomes play a crucial role in chronic stress‐mediated lung metastasis of breast cancer. Chronic stress‐induced TDEs are internalized by pulmonary neutrophils and strengthen neutrophil recruitment via the CXCL2 autocrine. In addition, the level of SP1 in TDEs increases, which favors the secretion of IL‐1β by neutrophils through the activation of the TLR4‐NFκβ pathway, ultimately aggravating lung metastasis of breast cancer. Collectively, this study provides a novel mechanism by which neutrophils within a pre‐metastatic niche acquire their inflamed phenotype and establishes an important link among neuroendocrine changes, exosomes, immunity, and metastasis.